2004
DOI: 10.1097/01.cmr.0000130007.54508.b2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antitumour activity of resveratrol in human melanoma cells sensitive or resistant to temozolomide

Abstract: Resveratrol, a polyphenol present in many plant species, exhibits a wide range of biological and pharmacological activities both in vitro and in vivo. It has been shown to exert a potent chemopreventive effect in carcinogenesis models and to induce cell growth inhibition and apoptosis in human tumour cells, including melanoma cells. Malignant melanoma is considered to be a chemotherapy-refractory tumour, and the commonly used anticancer drugs do not seem to modify the prognosis of metastatic disease. To furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
(47 reference statements)
1
32
0
1
Order By: Relevance
“…Both compounds have been found to inhibit numerous cell surface protein kinases and both exhibit cytotoxic effects in a variety of tumor cell lines [Zheng and Ramirez, 1999;Fuggetta et al, 2004;Larrosa et al, 2004;Pozo-Guisado et al, 2005]. These compounds have also been found to inhibit EC tube differentiation in vitro [Belleri et al, 2005], thus indirectly supporting the relevance of cell surface F 1 F O ATP synthase to angiogenesis and tumor biology.…”
Section: Atp Synthase: a Cell Surfacementioning
confidence: 85%
“…Both compounds have been found to inhibit numerous cell surface protein kinases and both exhibit cytotoxic effects in a variety of tumor cell lines [Zheng and Ramirez, 1999;Fuggetta et al, 2004;Larrosa et al, 2004;Pozo-Guisado et al, 2005]. These compounds have also been found to inhibit EC tube differentiation in vitro [Belleri et al, 2005], thus indirectly supporting the relevance of cell surface F 1 F O ATP synthase to angiogenesis and tumor biology.…”
Section: Atp Synthase: a Cell Surfacementioning
confidence: 85%
“…This could be the case of the combination with 5-fluorouracil (5-Fu) which is a classic drug used in colorectal and hepatoma chemotherapy. Indeed, it was reported that resveratrol can exert synergic effect with this drug to inhibit hepatocarcinoma cell proliferation by the induction of apoptosis [236,237].…”
Section: C) Resveratrol An Adjuvant For Chemo-sensitization and Radimentioning
confidence: 99%
“…Paeonia lactiflora, which belongs to the Paeoniaceae family, is known as one of the richest sources of various resveratrol derivatives [81]. These phytoestrogens are known to exert strong antioxidant activity [81] and to inhibit growth of several cancer cell lines [82,83], including a colon human cell line [84]. Recently, the antiproliferative effects of essential oils obtained from Platycladus orientalis on human renal adenocarcinoma and amelanotic melanoma cells have been reported [85].…”
Section: Resultsmentioning
confidence: 99%